The Effect of Firm-Level Investment on Inequality and Poverty around the World - Mehmet S. Tosun; Ethan D. Watson; Serhat Yildiz (Institute of Labor Economics (IZA), 2022)
This paper investigates the effect of firm-level investment on the levels of income inequality and poverty. Using a sample of firms from 87 countries for the period from 1979 to 2018, we document that firm-level investment is negatively associated with various measures of income inequality. This negative association is robust to alternative firm-level capital investment proxies, empirical model specifications, and a variety of country-level controls. Further evidence shows that firm-level investment is also negatively related to several measures of poverty. Overall, our results indicate that firm-level capital expenditures provide benefit to the poor and, thus, decreases income inequality. Our findings indicate that firm-level capital investment can be a valuable tool for countries that are aiming to achieve the United Nations' Sustainable Development Goals of reducing inequality and poverty. Our results may also be beneficial to policy makers as they consider a variety of regulatory and taxation measures that may constrain or help firm's ability to invest.
Keywords: D31; E22; I32; O15; O16; 330; income inequality; corporate capital expenditure; poverty; Sustainable Development Goals (SDGs)